Luteinizing Hormone-Releasing Hormone (LHRH)-Conjugated Cancer Drug Delivery from Magnetite Nanoparticle-Modified Microporous Poly-Di-Methyl-Siloxane (PDMS) Systems for the Targeted Treatment of Triple Negative Breast Cancer Cells. - Obayemi, J.D.; Osafo, S.A.; Eluu, S.C.; Yiporo, D.; Salifu, A.A.; et al. (Journal of Function Biomaterials, 2024)
Abstract: This study presents LHRH conjugated drug delivery via a magnetite nanoparticle-modified microporous Poly-Di-Methyl-Siloxane (PDMS) system for the targeted suppression of triple-negative breast cancer cells. First, the MNP-modified PDMS devices are fabricated before loading with targeted and untargeted cancer drugs. The release kinetics from the devices are then studied before fitting the results to the Korsmeyer–Peppas model. Cell viability and cytotoxicity assessments are then presented using results from the Alamar blue assay. Apoptosis induction is then elucidated using flow cytometry. The in vitro drug release studies demonstrated a sustained and controlled release of unconjugated drugs (Prodigiosin and paclitaxel) and conjugated drugs [LHRH conjugated paclitaxel (PTX+LHRH) and LHRH-conjugated prodigiosin (PG+LHRH)] from the magnetite nanoparticle modified microporous PDMS devices for 30 days at 37 ◦C, 41 ◦C, and 44 ◦C. At 24, 48, 72, and 96 h, the groups loaded with conjugated drugs (PG+LHRH and PTX+LHRH) had a significantly higher (p < 0.05) percentage cell growth inhibition than the groups loaded with unconjugated drugs (PG and PTX). Additionally, throughout the study, the MNP+PDMS (without drug) group exhibited a steady rise in the percentage of cell growth inhibition. The flow cytometry results revealed a high incidence of early and late-stage apoptosis. The implications of the results are discussed for the development of biomedical devices for the localized and targeted release of cancer drugs that can prevent cancer recurrence following tumor resection.
Research Article
Keywords: Conjugated Drugs; Sustained Drug Release; Cell Viability; Triple-Negative Breast Cancer; Magnetite; Poly-Di-Methyl-Siloxane (PDMS); Targeted And Localized Treatment